Undang-Undang Pesantren Sebagai Rekognisi Dan Implikasi Kebijakan Pemerintah Terhadap Pendidikan Pesantren Di Indonesia - Syarifah, Himmatus; Munandar, Aris (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
This paper examines the government's policy recognition of pesantren, which is the oldest Islamic education institution in Indonesia. Pesantren itself is defined as an educational institution that is community-based and founded by individuals, foundations, Islamic community organizations, and/or the community that instills faith and piety to Allah, promotes noble morals and upholds the teachings of Islam rahmatan lil'alamin which is reflected in humility, tolerance, balance, moderation, and other noble Indonesian values through education, Islamic preaching, exemplary, and community empowerment within the framework of the Unitary State of the Republic of Indonesia (NKRI). Historically, Syaikh Maulana Malik Ibrahim can be said to have laid the foundations of pesantren education in Indonesia. Pesantren in the early days of its establishment was a medium for spreading Islam and therefore had a major role in social change in Indonesian society until the birth of the Pesantren Law. This regulation has provided the direction of pesantren education policy in Indonesia (grand design) for the future in the field of Islamic religious education. The birth of this law is a breath of fresh air for the world of pesantren, besides that the Pesantren Law is a form of government recognition of pesantren education in Indonesia.